Analysis of the current status and associated factors of depressive symptoms in Chinese middle-aged and elderly stroke patients—based on CHARLS data - Yage Shi; Chenjun Liu; Xueting Sun; Dingding Li; Shuaiyou Wang; Xinyi Zhu; Kun Pan; Xiaoxia Chen; Huimin Zhang (Frontiers in Psychiatry, 2025)
BackgroundTo investigate the prevalence and associated factors of depressive symptoms in middle-aged and elderly stroke patients in China, and to provide reference for improving the mental health of middle-aged and elderly stroke patients in China.MethodsThe data for this study were drawn from the 2020 wave of the China Health and Retirement Longitudinal Study (CHARLS), and middle-aged and elderly stroke patients aged ≥45 years were considered as study subjects (n=988). A simplified version of the Epidemiological Survey Depression Scale score was used to determine depressive symptoms (≥10 points defined as depression) in the study population, and associated factors were analyzed using binary logistic regression.ResultsAmong the 988 middle-aged and elderly stroke patients, 547 (55.4%) had depressive symptoms and 441 (44.6%) did not. The results of binary logistic regression analysis showed that education level, history of alcohol consumption, sleep quality, loneliness, self-rated health status, self-rated memory status, life satisfaction, and ADL were the associated factors of depressive symptom in middle-aged and elderly stroke patients (P < 0.05).ConclusionThe study has shown that depressive symptoms in Chinese middle-aged and elderly stroke patients are associated with a variety of factors, and healthcare professionals should regularly assess with early recognition and take interventions to improve the disease.